MOVING TOWARD SUSTAINABLE CONSUMPTION IN ELECTRONICS DESIGN, PRODUCTION, AND RECYCLING (Utah Environmental Law Review; Vol 31 No 1 (2011), 2011)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} We live in a world of limited resources. Humanity is overshooting Earth's ecological limits, consuming resources and generating waste at an unsustainable rate. If everyone on Earth lived the lifestyle of the average American it would require five planets, according to Global Footprint Network. Business has the knowledge and skills to retool its operations to live within the ecological limits of the planet. But to achieve this lifestyle, according to a recent assessment by the World Business Council for Sustainable Development, huge changes will be needed in business practices, consumer behavior, and government policies to achieve it. The path towards sustainable production and consumption for business was sketched broadly in the seminal 1999 book Natural Capitalism . It called on business to develop design innovations to make far more efficient use of natural resources, recast industrial systems to more closely mimic nature, and to reinvest in Earth's "natural capital" to sustain and restore its resources. One important incremental step to promote more efficient use of resources is for companies to move towards greater responsibility for the full life cycle of products; this is especially important with complex high-technology goods that contain both valuable and toxic components.